Rolling-horizon algorithm for scheduling under time-dependent utility pricing and availability - Castro, Pedro (2011)
This work addresses the scheduling of continuous single-stage multiproduct plants with energy intensive processing tasks and time-dependent electricity cost and power supply. A new rolling horizon algorithm is proposed that consists of a planning model to predict the production levels and a continuous-time model for detailed scheduling. The results from a set of test problems from the literature show that the algorithm can generate global optimal solutions much more rapidly than standalone discrete or continuous-time formulations in problems involving unlimited power availability.